Household food security during Covid-19 pandemic in Daerah Istimewa Yogyakarta, Indonesia - Nurwulan Purnasari; Titisari Juwitangtyas; Iman Sabarisman (Center for Science and Technology, IAIN Surakarta, 2020)
Household food security in Indonesia depends on many factors. This study aims to describe household food security during the Covid-19 pandemic in Daerah Istimewa Yogyakarta (DIY). This research was conducted using a questionnaire for taking data. This study showed that there was a difference in household food security between the pre-pandemic of Covid-19 and during the pandemic of Covid-19. The hunger scale di DIY at the pre-pandemic of Covid-19 was 6% and increased during the pandemic of Covid-19 to 11%. It is showed that the financial crisis because of Covid-19 also influenced at increasing household food insecurity. As far as future research is concerned, the impact of food insecurity in vulnerable groups within the studied communities needs to be determined.